Manual Brew House Blend Coklat khas Indonesia - Hanna Daniati; R.A. Mochammad Deval; Ridwan Iskandar (STIEPAR YAPARI Bandung, 2020)
Experimental research in the form of making house blend chocolate by using chocolate originating from Indonesia, namely Java Srawana, Lampung Pesawaran and Sulawesi Celebes using the Manual Brew method using cezve tools. The goal is to get aspects of the original chocolate flavor image from chocolate blend and add interesting experiences in drinking original chocolate from Indonesia. The research method used is an experimental research method. By making 3 house blend chocolate recipes and tested on 50 panelists. The data collection method is carried out by distributing questionnaires to panelists. Data analysis methods used were organoleptic test, Variant Analysis (ANOVA) and t test, Tukey Ba, with the help of Microsoft Excel 2010 and SPSS.22 software (Statistical Product for Service Solution). The results of this study were obtained, house blend chocolate with the composition of Lampung Pesawaran 6gr, Java Srawana 6gr and Sulawesi Celebes 8gr, received by all panelists from the aspects of aroma, flavor, acidity, bitterness, astringent (taste), caramelly, creamy, texture. Produces a real chocolate flavor with a banana-flavored sweet and slightly bitter, then accompanied by the smell of vanilla.